Adoption of Tourist Mobile Applications: Motivating Factors for their Use, an Exploratory Study in Spanish Millennials - Sánchez-Torres, Javier A.; Arroyo-Cañada, Francisco-Javier; Argila-Irurita, Ana (Journal of Telecommunications and the Digital Economy, 2021)
The objective of this article is to examine factors that affect the attitude to and use of tourist mobile applications. In line with previous studies, an empirical model that integrates variables of a technological nature and others related to the design and architecture of tourist apps was proposed. An online survey of 156 millennials in Spain was carried out and the data were analysed using the partial least squares methodology. The results validated the hypotheses proposed in the model, achieving a high level of statistical prediction. The results supported that, when choosing a tourist mobile application, tourists take into consideration design aspects, such as visual design and navigation design; personal aspects, such as perceived personal outcome expectations, perceived enjoyment and subjective norm; and operational aspects, such as effort expectations, performance expectations, and conversion rate.